Dynamically Controlled Iridescence of Cholesteric Cellulose Nanocrystal Suspensions Using Electric Fields - Frka-Petesic, Bruno (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.